2017
DOI: 10.1038/ijo.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body composition and serum inflammatory markers on the functional muscle–bone unit in premenopausal women

Abstract: BACKGROUND/OBJECTIVES: A number of recent studies dealing with the relationship between the effects of high body mass (BM) and fat mass (FM) on bone mass and strength exhibit a range of contrasting variations in their findings. These diverse findings have led to an ongoing controversy as to whether high BM and FM positively or negatively affect bone mass and strength. Excessive FM and the associated low-grade inflammation might overturn the higher mechanical stimulus arising from a higher BM. Therefore, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For comparison purposes, Swiss men with a mean age of 42 years had a relative body fat percentage of 21.0% [68], which is a slightly elevated value. In a sample of Swiss women ( n = 64) with a mean age of 27 years, more than two-thirds (70.3%) had a body fat percentage ≥30% [69], which indicates the presence of a high percentage of plump women. Since fat mass is the strongest predictor of the variability of resting VO 2 [17], such differences in body composition (higher relative FFM in the present study) might explain the higher individual 1-MET value of the controls compared to the values reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison purposes, Swiss men with a mean age of 42 years had a relative body fat percentage of 21.0% [68], which is a slightly elevated value. In a sample of Swiss women ( n = 64) with a mean age of 27 years, more than two-thirds (70.3%) had a body fat percentage ≥30% [69], which indicates the presence of a high percentage of plump women. Since fat mass is the strongest predictor of the variability of resting VO 2 [17], such differences in body composition (higher relative FFM in the present study) might explain the higher individual 1-MET value of the controls compared to the values reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological strain of human weight-bearing bone is generally <2,000 µε (12). In Frost's bone function adaptability model, 50-2,500 µε is considered strain in the physiological range (13,14). Previous studies of osteoblasts cultured in vitro revealed that mechanical tensile strain of 2,500 µε at 0.5 Hz could promote osteogenic differentiation and improve osteogenic function (15)(16)(17), and that mechanical tensile strain of 2,500 µε at 0.5 Hz could be regarded as normal physiological load (17).…”
Section: Conditioned Medium Of Pc-3 Prostate Cancer Cells Affects Mic...mentioning
confidence: 99%
“…Results of a large study also showed that a pro-inflammatory diet was associated with higher body mass index (BMI) z-score, wrist circumference, waist circumference (WC), hip circumference (HC), and parental BM (17). Moreover, higher serum levels of anti-inflammatory markers are considered to play a protective role on fat free mass (FFM) (18,19). Given that there is currently no study that has evaluated the association between DII and muscle and anthropometric indices, in an Iranian population, the aim of the present study was to analyze the relationship between DII and muscle endurance, strength, and body composition in middle aged adults in Iran.…”
Section: Introductionmentioning
confidence: 99%